Silicon Dioxide Functionalized with Oxygen–Containing Groups for Enhanced BCl3 Adsorption - Miaolei Zhang; Jianhua Liu; Guoqiang Huang (Adsorption Science & Technology)
Boron chloride in the chlorosilane is hard to remove and directly impacts the quality of polysilicon produced by improved Siemens method. Silicon dioxide functionalized with mannitol and citric acid successfully removed boron chloride in organic solution. The effects of immersion concentration and drying temperature were studied to attain the best adsorption performance. The sorption phenomenon was described well by pseudo-second-order kinetic model and Langmuir adsorption isotherm; particle diffusion model proved that the adsorption on the active adsorption site was the rate determining step, with the formation of boronic esters. Thermal stability and degradation kinetic of the adsorbents were investigated by thermogravimetric analysis. The characterization results of Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray energy spectrometry, and BET showed the silicon dioxide was successfully functionalized by oxygen-containing functional groups, leading to be a better and safer substitute to traditional boron-selective chelating resin.